ภาวะผู้นำทางวิชาการของผู้บริหารสถานศึกษาที่ส่งผลต่อประสิทธิผลของโรงเรียน สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาสกลนคร เขต 2 - Klaifon, Ornuma; Jantarak, Suphirun; Phengsawat, Waro (Journal of Graduate School Sakon Nakhon Rajabhat University, 2023)
The purposes of this research were to 1) examine the level of Instructional leadership of school administrators, 2) study the level of school effectiveness, 3) identify the relationship between instructional leadership of school administrators and the school effectiveness, 4) determine the predictive equation of instructional leadership of school administrators affecting the school effectiveness, and 5) establish guidelines for developing instructional leadership of school administrators affecting the effectiveness of schools under Sakon Nakhon Primary Educational Service Area Office 2. The samples, obtained through multi-stage sampling, consisted of school administrators and heads of the academic affairs division, yielding a total of 264 participants. The research instruments for data collection were sets of 5-level rating scale questionnaires on instructional leadership of school administrators with IOC ranging from .60 to 1.00, the discriminative power ranging from .41 to .88, and the reliability of .99, and the school effectiveness with IOC ranging from .80 to 1.00, the discriminative power ranging from .58 to .87, and the reliability of .97. The statistics for data analysis were frequency, percentage, mean, standard deviation, Pearson’s product-moment correlation coefficient, and Stepwise multiple regression analysis. The results of this study showed that: 1) The level of instructional leadership of school administrators was at a high level both in whole aspects and each aspect, 2) The level of school effectiveness was at a high level both in whole aspects and each aspect,3)The relationship between Instructional leadership of school administrators and the school effectiveness showed positive correlation at the .01 level of significance, 4) The instructional leadership of school administrators in terms of setting the conducive atmosphere for learning (X4), supervision, monitoring and evaluation of teaching and learning management (X6), and setting vision, goals, and missions (X1), were able to predict the school effectiveness at the .01 level of significance, with the predictive power of 72.20. The predictive equation could be summarized in raw and standardized scores as follows: Y' = .832 + .320 X4 + .334 X6 + .150 X1 and Z'y = .378 Z4 + .373 Z6 + .165 Z1, and 5) Guidelines for developing instructional leadership of school administrators affecting the school effectiveness encompassed three aspects with 15 approaches. These aspects included creating a conducive atmosphere for learning with five approaches, supervision, monitoring, and evaluation of teaching and learning management with five approaches, and setting vision, goals, and missions with five approaches. The guidelines were formulated based on research findings related to the instructional leadership of school administrators, which could predict the school effectiveness. These guidelines were established as developmental principles following the reviews of the five experts.